Sinapic acid attenuated nephrotoxicity against Cyclophosphamide in mice model: A histochemical, immunohistochemical and histopathological evaluation - Saeed Raoof; Shiva Rezaei; Mehryar Zargari; Masooreh Mirzaei; Seyed Jalal Hosseinimehr; Abbasali Karimpour Malekshah; Fereshteh Talebpour Amiri (Iranian Journal of Basic Medical Sciences)
Objective(s): Cyclophosphamide (CP) is a chemotherapeutic drug used to treat various tumors. It causes nephrotoxicity by producing reactive oxygen species. Sinapic acid (SA) exhibits anti-oxidant, antiapoptotic, and anti-inflammatory activities at low doses as a phenylpropanoid. This study aimed to investigate the protective effects of SA on SP-induced renal injury. Materials and Methods: Forty-eight BALB/c mice were randomly divided into control, SA (for seven consecutive days, with two doses of 5 and 10 mg/kg), CP (single dose, 200 mg/kg), and CP + SA (5 and 10 mg/kg). On the 10th day of the study, mice were examined by renal function markers (Urea and Creatinine), oxidative stress markers (MDA and GSH), histopathological, and immunohistochemical assays (caspase-3 and NF-kB kidney). Results: MDA levels increased and GSH levels decreased significantly in CP-treated mice. In addition, the histopathological structure of the kidney tissue in CP-treated mice showed significantly severe kidney tissue damage associated with increased urea and creatinine. The administration of SA in CP-treated mice significantly reduced serum urea and creatinine concentrations. In addition, the immunohistochemical staining of caspase- 3 and NF-kB decreased significantly in the CP + SA group compared to CP-treated mice. Conclusion: Overall, our study suggests that sinapic acid, a substance with antioxidant, antiapoptotic, and anti-inflammatory properties, can be used as a complementary therapy to protect nephrotoxicity against CP.